Strategy for Enhancing Organizational Citizenship Behavior (OCB) Through Strengthening Organizational Culture, Transformational Leadership, and Work Motivation at the Soekarno-Hatta Type C Main Customs and Excise Service Office Hatta - Insan Pribadi; Nancy Yusnita; Yayan Hadiyat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze strategies for improving Organizational Citizenship Behavior (OCB) through the strengthening of organizational culture, transformational leadership, and work motivation at the Soekarno-Hatta Type C Main Customs and Excise Service Office. The research method used is a quantitative approach using a survey method. The analysis technique used is Structural Equation Modeling (SEM). The population in this study consists of operational inspection employees, including functional Customs and Excise inspectors who are civil servants (ASN) within the Soekarno-Hatta Type C Main Customs and Excise Office, with a sample size of 138 respondents using the Probability Sampling technique. The results of the study show that organizational culture has a direct, positive, and significant effect on work motivation but does not have a significant effect on OCB. Transformational leadership has a direct, positive, and significant effect on both work motivation and OCB. Work motivation has a direct, positive, and significant effect on OCB. In addition, it was found that work motivation significantly mediates the relationship between organizational culture and OCB as well as between transformational leadership and OCB, although its effectiveness is lower compared to the direct effect of transformational leadership on OCB. These findings affirm that strengthening organizational culture and transformational leadership can enhance work motivation, which ultimately has a positive impact on improving employees' OCB. The implications of this research are expected to serve as a foundation for designing organizational policies to promote proactive and collaborative work behavior within the Customs and Excise environment.